2019
DOI: 10.3892/mco.2019.1895
|View full text |Cite
|
Sign up to set email alerts
|

The association between statins and colorectal cancer stage in the Women's Health Initiative

Abstract: The anticarcinogenic effect of statins may reduce the metastatic potential of cancer cells leading to ‘stage migration’, with users more likely diagnosed with early rather than late stage cancer. The association between prior statin use and colorectal cancer (CRC) stage at diagnosis in the Women's Health Initiative (WHI) was investigated. The study population included 132,322 post-menopausal women, among which there were 2,628 pathologically confirmed cases of in situ (3.3%), localized (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Possible reasons include that these trials were designed to estimate the improvement in the effectiveness of other first-line drugs, not the effectiveness of statins alone, and more RCTs are needed to validate the robustness of our findings. In addition, accumulating data suggested that lipophilic statins provide a stronger protective effect than hydrophilic statins (63)(64)(65). However, the hydrophilic group displayed a lower hazard ratio in this study, probably because that most of the observational studies did not clarify statin types in their studies, which limited the number of included studies in this subgroup analysis.…”
Section: Discussionmentioning
confidence: 66%
“…Possible reasons include that these trials were designed to estimate the improvement in the effectiveness of other first-line drugs, not the effectiveness of statins alone, and more RCTs are needed to validate the robustness of our findings. In addition, accumulating data suggested that lipophilic statins provide a stronger protective effect than hydrophilic statins (63)(64)(65). However, the hydrophilic group displayed a lower hazard ratio in this study, probably because that most of the observational studies did not clarify statin types in their studies, which limited the number of included studies in this subgroup analysis.…”
Section: Discussionmentioning
confidence: 66%
“…The inhibition of isoprenoids synthesis mediated by statins also contributes to apoptosis induction and prevents the development of the cell cycle in different types of cancer cells [28]. In many cancers, including melanoma, extrahepatic cholangiocarcinoma, pancreatic adenocarcinoma, non-muscle-invasive bladder cancer, hepatocellular carcinoma, thymic carcinoma, renal cell carcinoma, and in breast, colorectal, liver, lung, and prostate cancers, the effects of statins on cancer risk, recurrence and survival have been confirmed in preclinical and clinical studies [29][30][31][32][33][34][35][36][37]; however, some of the large-scale reviews, including systematic review and meta-analysis, have not clearly shown any beneficial impact of statins against cancer [38][39][40].…”
Section: Potential Antitumor Mechanisms Of Statinsmentioning
confidence: 99%